2015
DOI: 10.1128/genomea.00745-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Vibrio VPAP30, Isolated from an Episode of Massive Mortality of Reared Larvae of the Scallop Argopecten purpuratus

Abstract: We report here the 5.167-Mbp draft genome sequence of Vibrio VPAP30, isolated from an Argopecten purpuratus larval culture. Vibrio VPAP30 is the etiological agent of a vibriosis outbreak causing a complete collapse of a larval culture of the scallop A. purpuratus, which occurred in a commercial hatchery in Chile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Although various V. coralliilyticus strains were previously miss-identified as V. tubiashii , sequence analysis performed on the VPAP30 strain clearly differentiated this strain to the V. coralliilyticus species, despite the apparent carriage of a metalloprotease-encoding gene similar to the detected in V. coralliilyticus ( Rojas et al, 2015b ). Furthermore, many studies reported V. coralliilyticus as an opportunistic pathogen against larvae of various mollusc species, including Greenshell mussel Perna canaliculus , great scallop Pecten maximus and oysters Crassostrea gigas, Crassostrea virginica , and Ostrea edulis ( Kesarcodi-Watson et al, 2009 , 2012 ; Genard et al, 2013 ; Richards et al, 2015 ), prompting the necessity for adequate differentiation between V. tubiashii and V. coralliilyticus species when they are involved in mollusc larval pathologies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although various V. coralliilyticus strains were previously miss-identified as V. tubiashii , sequence analysis performed on the VPAP30 strain clearly differentiated this strain to the V. coralliilyticus species, despite the apparent carriage of a metalloprotease-encoding gene similar to the detected in V. coralliilyticus ( Rojas et al, 2015b ). Furthermore, many studies reported V. coralliilyticus as an opportunistic pathogen against larvae of various mollusc species, including Greenshell mussel Perna canaliculus , great scallop Pecten maximus and oysters Crassostrea gigas, Crassostrea virginica , and Ostrea edulis ( Kesarcodi-Watson et al, 2009 , 2012 ; Genard et al, 2013 ; Richards et al, 2015 ), prompting the necessity for adequate differentiation between V. tubiashii and V. coralliilyticus species when they are involved in mollusc larval pathologies.…”
Section: Discussionmentioning
confidence: 94%
“…It must be noted that a metalloprotease encoding gene similar to vtpA was detected in the genome of V . tubiashii VPAP30 ( Rojas et al, 2015b ). Moreover, Hasegawa et al (2008) demonstrated that metalloprotease inhibitors severely reduce the toxicity of ECPs produced by two strains recently identified as V. coralliilyticus ( Wilson et al, 2013 ; Richards et al, 2014 ), but previously miss-identified as V. tubiashii , on Pacific oyster larvae.…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that a metalloprotease encoding gene similar to vtpA was detected in the genome of this pathogenic strain (formerly V . tubiashii VPAP30) (Rojas et al, 2015b). Moreover, Hasegawa et al (2008) demonstrated that metalloprotease inhibitors severely reduce the toxicity of ECPs produced by 2 strains recently identified as V. coralliilyticus (Wilson et al, 2013; Richards et al, 2014), but previously miss-identified as V. tubiashii , on Pacific oyster larvae.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, recurrent mortality episodes are described as a result of virus or Vibrio-like bacteria infecting bivalve hatcheries and nurseries (Renault and Arzul, 2001;Dubert et al, 2015;Rojas et al, 2015) and reducing commercial production by approximately 40% as reported for French farming facilities of Pacific oyster (Crassostrea gigas) since 2008 (Pernet et al, 2014).…”
Section: Introductionmentioning
confidence: 99%